A Comprehensive Mapping of Conflict and Conflict Resolution: A Three Pillar Approach - Sandole, Dennis J. D. (NSUWorks, 1998)
Excerpt As I contemplate the rise worldwide in intrastate (in contrast to interstate) conflicts (see, e.g., van Creveld, 1991 and K. Holsti, 1996), leading to Yugoslavian and Rwandan-type situations, I sense the need to do something about them. As Rousseau has said, "wars occur because there is nothing to prevent them" (cited in Waltz, 1959, p. 232). And quite frankly, there are few, if any, mechanisms worldwide relevant to staving off a future Yugoslavia, Rwanda, and the like (see Lund, 1996): witness the unfolding of the violent Albanian-Serbian conflict in Kosovo into a possible, wider Balkan war (see, e.g., Nordland and Watson, 1998; Finn, 1999; Dinmore, 1999a, 1999b)!